A mosaic of induced and non-induced branches promotes variation in leaf traits, predation and insect herbivore assemblages in canopy trees - Volf, Martin; Volfová, Tereza; Seifert, Carlo L; Ludwig, Antonia; Engelmann, Rolf A; Jorge, Leonardo Ré; Richter, Ronny; Schedl, Andreas; Weinhold, Alexander; Wirth, Christian; van Dam, Nicole M (Ecology letters, 2022)
Forest canopies are complex and highly diverse environments. Their diversity is affected by pronounced gradients in abiotic and biotic conditions, including variation in leaf chemistry. We hypothesised that branch-localised defence induction and vertical stratification in mature oaks constitute sources of chemical variation that extend across trophic levels. To test this, we combined manipulation of plant defences, predation monitoring, food-choice trials with herbivores and sampling of herbivore assemblages. Both induction and vertical stratification affected branch chemistry, but the effect of induction was stronger. Induction increased predation in the canopy and reduced herbivory in bioassays. The effects of increased predation affected herbivore assemblages by decreasing their abundance, and indirectly, their richness. In turn, we show that there are multiple factors contributing to variation across canopies. Branch-localised induction, variation between tree individuals and predation may be the ones with particularly strong effects on diverse assemblages of insects in temperate forests.
Keywords: canopy; Insecta; trophic interactions; stromy; diversity; herbivory; býložravci; Plant Leaves; hmyz; Predatory Behavior; vertical stratification; Trees; polyphenols; predátorské chování; zvířata; lesy; induced defences; Herbivory; volatile organic compounds; listy rostlin; predators; Forests; Animals